Simultaneous HPLC Determination of Chlordiazepoxide and Mebeverine HCl in the Presence of Their Degradation Products and Impurities - Rania N. El-Shaheny; Fathalla F. Belal (Journal of Chemistry)
A simple, rapid, and sensitive RP-HPLC method was developed and validated for the simultaneous determination of chlordiazepoxide (CDO) and mebeverine HCl (MBV) in the presence of CDO impurity (2-amino-5-chlorobenzophenone, ACB) and MBV degradation product (veratric acid, VER). Separation was achieved within 9 min on a BDS Hypersil phenyl column (4.5 mm × 250 mm, 5 µm particle size) using a mobile phase consisting of acetonitrile: 0.1 M potassium dihydrogen phosphate: triethylamine (35 : 65 : 0.2, v/v/v) in an isocratic mode at a flow rate of 1 mL/min. The pH of the mobile phase was adjusted to 4.5 with orthophosphoric acid and UV detection was set at 260 nm. A complete validation procedure was conducted. The proposed method exhibited excellent linearity over the concentration ranges of 1.0–100.0, 10.0–200.0, 2.0–40.0, and 2.0–40.0 µg/mL for CDO, MBV, VER, and ACB, respectively. The proposed method was applied for the simultaneous determination of CDO and MBV in their coformulated tablets with mean percentage recoveries of 99.75 ± 0.62 and 98.61 ± 0.38, respectively. The results of the proposed method were favorably compared with those of a comparison HPLC method using Student t-test and the variance ratio F-test. The chemical structure of MBV degradation product was ascertained by mass spectrometry and IR studies.